Growth Performance and Profitability Analysis of Five-Chicken Strains in South Western Nigeria - Atansuyi , A.J.; Ilori, O.D.; Chineke, C.A.; Adebayo, O.T. (International Journal of Poultry Science, 2022)
Objective: This experiment was conducted to investigate the growth performance, carcass and organ traits and profitability of five-chicken strains in South-western Nigeria. Materials and Methods: A total of 300 birds comprising five strains, 60 birds per strain, were used for the experiment. Each strain was made of ratio 30:30 males to females. The experiment spanned through eight weeks and the birds were distributed based on their strains and sexes into ten treatments of 30 birds with three replicates of 10 birds each. At the end of 8th week, 12 birds (6 males and6 females) were randomly selected for analyses. Results: Analytical results showed that genotype significantly influenced (p<0.05) the initial weight (IWT), final weight (FWT), total weight gain (TWG), total feed intake (TFI) and feed conversion ratio (FCR). Hubbard birds (HB) consumed the highest quantity of feed (3,084.61 g), utilized the feed more efficiently with FCR of 1.60, gained more body weight (1930.30 g) and showed more final weight (1966.80 g) than the Nigerian indigenous genotypes. However, among the Nigerian chicken genotypes, Fulani ecotype (FE) consumed more feed (3012.40 g), utilized the feed more efficiently, gained more body weight (1812 g) and weighed heaviest (1840.99 g). As expected, the effect of genotype on carcass characteristics showed that Hubbard meat type chicken strain had the highest and significant (p<0.05) yields among all the carcass traits. Nevertheless, Fulani ecotype (FE) took the lead among the parameters for the indigenous chickens, followed by naked neck (NN) and least with normal feather (NF). The results also showed a significant difference (p<0.05) in organ characteristics of the chicken genotypes. Profitability analysis indicated that the total revenue (₦135,000) accrued from sale of Hubbard broiler chickens was slightly higher than the Fulani ecotype (₦127,500) which is an indigenous chicken. The four profitability indicators used to measure the extent of returns from the production of the 5-chicken strains were gross margin, net farm income, rate of return on investment (RROI) and benefit cost ratio. For Fulani ecotype, the gross margin, net farm income, rate of return on investment (RROI) and benefit cost ratio were estimated to be ₦95,000, ₦90,726.68, 246.72% and 3.47 respectively. The corresponding values for the Hubbard broiler chicken were ₦102, 500, ₦98, 226.68, 267.11% and 3.67. These results were comparable and do not show any considerable difference in profitability between Fulani ecotype and Hubbard broiler chickens. The higher values of profitability indicators suggested that raising of Fulani ecotype as meat type chicken is more profitable for poultry farmers compare to other Nigerian indigenous chickens. Conclusion: The study suggested that Fulani ecotype strains could be regarded as heavy breed chicken and be incorporated into a meat producing indigenous chicken with desired improvement.